Effectiveness of Standard Oral Care Plan During Hospital Stay in Individuals With Brain Injury - Kothari, Simple F.; Nascimento, Gustavo G.; Jakobsen, Mille B.; Nielsen, Jørgen F.; Kothari, Mohit (Frontiers in Neurology, 2021)
Objective: To investigate the effectiveness of an existing standard oral care program (SOCP) and factors associated with it during hospitalization in individuals with acquired brain injury (ABI). Material and Methods: Sixty-one individuals underwent a SOCP for four weeks in longitudinal observational study. Rapidly noticeable changes in oral health were evaluated by performing plaque, calculus, bleeding on probing (BOP) and bedside oral examination (BOE) at week 1 and 5. Individuals’ brushing habits, eating difficulties, and onset of pneumonia were retrieved from their medical records. Association between oral-health outcomes to systemic variables were investigated through multilevel regression models. Results: Dental plaque (P=0.01) and total BOE score (P<0.05) decreased over time but not the proportion of dental calculus (P=0.30), BOP (P=0.06) and tooth brushing frequency (P=0.06). Reduction in plaque, and BOE over time were negatively associated with higher periodontitis score at baseline (coef. -6.8; -1.0) respectively, which in turn were associated with an increased proportion of BOP (coef. ≈ 15.0). Increased proportion of calculus was associated with eating difficulties (coef. 2.3) and onset of pneumonia (coef. 6.2). Conclusions: Nursing care has been fundamental in improving oral health, especially reducing dental plaque and BOE scores. However, our findings indicate a need for improving the existing SOCP through academic-clinical partnerships. Clinical Relevance: Early introduction of oral care program to brain injured individuals is beneficial in reducing plaque accumulation and improving oral health.